2012
DOI: 10.1515/hmbci-2012-0028
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fermented soy (FSWW08) on blood hematology and cachexia in cancer patients

Abstract: In cancer patients, appetite and immune status are significantly weakened. Two experimental fermented formulations without (group A, named as FSWW08) and with (group B, FSWW08) an extract from yam root were investigated against a placebo formulation with casein (group C) in a clinical study conducted in six cancer hospitals where cancer patients underwent radio or chemotherapy (patients undergoing radiation therapy n=78, patients undergoing chemotherapy n=184, total 262). IgG and IgA were increased by formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 39 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…The study protocol was reviewed by a local institutional review board (IRB) to protect the rights of patients, safety and well-being of humans involved in a clinical trial by reviewing all aspects of the trial and approving its startup and was published previously [24,39,40]. All patients had to sign an Informed Consent Form after the physician explained the study and he read the informed consent form where the study goal was outlined in a written form, in which the study was outlined and participation was voluntarily and it was explained individually to all patients that they could leave the study at any time even without explanation.…”
Section: A Irbmentioning
confidence: 99%
See 3 more Smart Citations
“…The study protocol was reviewed by a local institutional review board (IRB) to protect the rights of patients, safety and well-being of humans involved in a clinical trial by reviewing all aspects of the trial and approving its startup and was published previously [24,39,40]. All patients had to sign an Informed Consent Form after the physician explained the study and he read the informed consent form where the study goal was outlined in a written form, in which the study was outlined and participation was voluntarily and it was explained individually to all patients that they could leave the study at any time even without explanation.…”
Section: A Irbmentioning
confidence: 99%
“…This paper therefore systematically investigates the effect of fermented soy bean formulation on cancer cells in vitro, as was shown by others also, in vivo in CTC extracted from blood from cancer patients, which has not been shown before. We detected and reported earlier that the effectiveness of chemotherapy was increased by fermented soy formulation, side effects were reduced, and survival increased [39,40]. This study investigates in vitro whether a combination of the classic cytotoxic compound doxorubicin may be combined with fermented soy bean and counterbalance some of the side effects of classical chemotherapy on the genetic level.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…cytokines ( Figures 10-13) (37). A clinical trial with breast cancer patients revealed a reduction of Th1 cytokines and a reduction of symptoms related to Th1 cytokines after consuming fermented soy ( Figure 14) (38,39). It is now recognized that cytokines in the blood of cancer patients are released from immune cells within the tumor, increasing the surrounding capillary membrane permeability, leading to the spread of tumor cells and cytokines, and causing metastasis and discomfort ( Figure 15) (40)(41)(42)(43)(44)(45)(46).…”
Section: Figurementioning
confidence: 99%